Risk of Adverse Events After Anti-TNF Treatment for Inflammatory Rheumatological Disease. A Meta-Analysis - Li, Ju; Zhang, Zhongyuan; Wu, Xinhua; Zhou, Jie; Meng, Deqian; Zhu, Ping (Frontiers in Pharmacology, 2021)
Background: Adalimumab, golimumab, infliximab, certolizumab, and etanercept are five anti-tumor necrosis factor (anti-TNF) medicines that have been approved for use in rheumatology. Apart from their well-established therapeutic usefulness, -it is unclear to what extent -they are linked to an increased risk of various side effects. The present meta-analysis was carried out to assess the risk of infection and other side effects after anti-TNF- α for the treatment of rheumatoid arthritis, psoriatic arthritis, and ankylosing spondylitis. Methods: We searched PubMed, Cinahl (via Ebsco), Scopus, and Web of Sciences databases for trials comparing anti-TNF medications to placebo or no therapy in adult patients with rheumatoid arthritis, psoriatic arthritis, or ankylosing spondylitis from August 2006 to August 2020. A total of 23 articles were used for meta-analysis. The Cochrane Collaboration’s risk of bias tool was used to assess the methodological quality of the included studies. In addition, a random-effects model was used to calculate the pooled odds ratio, and Forest plots were constructed to determine the risk of infections and cancer following the use of anti-TNF treatment. Results: Treatment with anti-TNFα agents resulted in an increase in the risk of serious infections (OR: 1.72, 95% CI: 1.56-1.90, P<0.00001) and an increase in cancer risk (OR: 1.36, 95% CI: 1.20-1.53, P<0.00001) whereas the risk of developing tuberculosis was not significantly different with anti-TNFα agents versus those without treatment with anti-TNFα agents (OR: 2.55, 95% CI: 0.40-16.23, P=0.32). The risk of bias of the included studies was unclear to high across most domains, and there was evidence of publication bias for most outcomes. Conclusion: The present meta-analysis suggests an increased risk of infectious adverse events, including overall adverse events and cancer following anti-TNFα treatment, whereas the risk of tuberculosis was not significantly different. Although anti-TNF agents have shown promise to treat inflammatory conditions, their use should be balanced by the risk-benefit ratio as suggested by the meta-analysis.